Clinical performance of non-invasive prenatal testing (NIPT) using targeted cell-free DNA analysis in maternal plasma with microarrays or next generation sequencing (NGS) is consistent across multiple controlled clinical studies - Stokowski, Renee; Wang, Eric; White, Karen; Batey, Annette; Jacobsson, Bo; Brar, Herb; Balanarasimha, Madhumitha; Hollemon, Desiree; Sparks, Andrew; Nicolaides, Kypros; Musci, Thomas J. (Prenatal diagnosis, 2015)
Objective To evaluate the clinical performance of non‐invasive prenatal testing for trisomy 21, 18, and 13 using targeted cell‐free DNA (cfDNA) analysis. Methods Targeted cfDNA analysis using DANSR™ and FORTE™ with microarray quantitation was used to evaluate the risk of trisomy 21, 18, and 13 in blinded samples from 799 singleton, twin, natural, and IVF pregnancies. Subjects either had fetal chromosome evaluation by karyotype, FISH, QF‐PCR, or karyotype for newborns with suspected aneuploidy at birth. The results of targeted cfDNA analysis were compared to clinical genetic testing outcomes to assess clinical performance. Results Targeted cfDNA analysis with microarray quantification identified 107/108 trisomy 21 cases (99.1%), 29/30 trisomy 18 cases (96.7%), and 12/12 trisomy 13 cases (100%). The specificity was 100% for all three trisomies. Combining this data with all published clinical performance studies using DANSR/FORTE methodology for greater than 23 000 pregnancies, the sensitivity of targeted cfDNA analysis was calculated to be greater than 99% for trisomy 21, 97% for trisomy 18, and 94% for trisomy 13. Specificity for each trisomy was greater than 99.9%. Conclusion Targeted cfDNA analysis demonstrates consistently high sensitivity and extremely low false positive rates for common autosomal trisomies in pregnancy across quantitation platforms. © 2015 Ariosa Diagnostics Inc. Prenatal Diagnosis published by John Wiley & Sons, Ltd. What's already known about this topic? NIPT using targeted cfDNA analysis with NGS has high sensitivity and specificity for fetal trisomy 21 and other autosomal trisomies. What does this study add? This study establishes the high sensitivity and specificity of NIPT using targeted cfDNA analysis with a microarray quantitation platform, and demonstrates that clinical performance is based on the targeted cfDNA analysis method rather than the quantitation method, as the performance using microarray is comparable with performance from previous NGS studies.